АТРОФ ТАБИИЙ МУҲИТНИНГ РАДИОАКТИВ ИФЛОСЛАНИШИ ОҚИБАТИДА ЮЗАГА КЕЛАДИГАН ФУҚАРОЛИК-ҲУҚУҚИЙ ЖАВОБГАРЛИККА ОИД МАСАЛАЛАР - Бабаназаров, К.Р. (SCIENCE and SOCIETY, 2017)
The article deals with the criteria and norms of legislative acts regulations in legal liability. In the article the author also examines legal significance and types of responsibility in the field of providing radiation safety.